2005
DOI: 10.1113/expphysiol.2005.030734
|View full text |Cite
|
Sign up to set email alerts
|

Actions of TNF‐α on glutamatergic synaptic transmission in the central nervous system

Abstract: Increasing attention is being paid to the role of inflammatory and immune molecules in the modulation of central nervous system (CNS) function. Tumour necrosis factor-α (TNF-α) is a pro-inflammatory cytokine, the receptors for which are expressed on neurones and glial cells throughout the CNS. Through the action of its two receptors, it has a broad range of actions on neurones which may be either neuroprotective or neurotoxic. It plays a facilitatory role in glutamate excitotoxicity, both directly and indirect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
249
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 373 publications
(261 citation statements)
references
References 79 publications
7
249
0
2
Order By: Relevance
“…Tumor necrosis factor-alpha and other cytokines have been postulated to impair learning and memory in a number of neuropathological conditions including CCI (Pickering et al, 2005;Scherbel et al, 1999), and to play a physiological role in normal brain function by modulating key elements of synaptic transmission involved in memory formation and learning (Albensi and Mattson, 2000). Mice with non-functional Fas on the MRL background have spatial learning deficits associated with autoimmunity and brain mononuclear infiltrates (Sakic et al, 1997); however, direct evidence that Fas participates in physiological or pathological learning and memory has not, to our knowledge, been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factor-alpha and other cytokines have been postulated to impair learning and memory in a number of neuropathological conditions including CCI (Pickering et al, 2005;Scherbel et al, 1999), and to play a physiological role in normal brain function by modulating key elements of synaptic transmission involved in memory formation and learning (Albensi and Mattson, 2000). Mice with non-functional Fas on the MRL background have spatial learning deficits associated with autoimmunity and brain mononuclear infiltrates (Sakic et al, 1997); however, direct evidence that Fas participates in physiological or pathological learning and memory has not, to our knowledge, been reported.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-␣ also has direct effects on glutamate transmission, such as by increasing the expression of AMPA receptors on synapses. 23 In addition, we previously presented evidence that NMDA blocker can reduce endogenous tissue plasminogen activator (tPA) and MMP-9 expressions. 11 In the present study, we found that GLT-1 upregulation reduced the expressions of TNF-␣, FasL, and MMP-9.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of evidence describes neurotoxic roles for TNF-␣ within the CNS (48 -50), as well as its ability to affect long-term potentiation and learning (51)(52). For chemokines such as MIP-1␣ and KC, it is likely that their production by plaque-surrounding cells results in the recruitment and accumulation of astrocytes and microglia in an attempt to phagocytose the plaque, thereby creating a vicious cycle of inflammation resulting in a chronic glial inflammation and ultimately neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%